What motivates firms to adopt a green supply chain and how much does it matter? - Wang, Mengmeng; Zhang, Guocheng (Frontiers in Environmental Science, 2023)
This study integrates the elaboration likelihood model, institutional theory, and the image management perspective to identify the internal and external forces that can effectively drive firms to adopt a green supply chain. Using survey data from a sample of 246 firms in the Chinese manufacturing sector, we empirically examine how the internal green process and green product innovation of firms and different types of external institutional pressures contribute to their adoption of a green supply chain, which in turn can explain the variation in their environmental and new-product development performance. Results of our structural equation modeling analysis reveal that the internal green process and green product innovation of firms and three types of external institutional pressures (i.e., coercive, normative, and mimetic pressures) play an important role in driving green supply chain adoption. Moreover, firms can improve their environmental and new-product development performance by adopting a green supply chain. In addition, though the image management motivation of firms tends to play a negative moderating role in the relationship between their green process innovation and green supply chain adoption, such motivation positively moderates the contribution of coercive pressure to their green supply chain adoption. Our findings can help explain why emerging-market firms tend to adopt a green supply chain and do not follow the pattern predicted by classical strategic management theories. The results of our study clearly demonstrate the determinants and consequences of the adoption of a green supply chain of firms and confirm that their green supply chain adoption can exert a positive effect on their environmental and new-product development performance. Overall, our research highlights the importance of recognizing internal innovation and external institutional forces in driving the green supply chain adoption of firms, which in turn will contribute to their environmental and new-product development performance. In this regard, our study extends the stream of research on green supply chains and sheds new light on the importance of abandoning the conventional supply chain and adopting a green one. Our study also provides important implications for research, practice, and policymaking.